2021
DOI: 10.3390/biomedicines9050548
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Mesenchymal Stem Cell-Delivered Oncolytic Virus with Prodrug Activation Increases Efficacy and Safety of Colorectal Cancer Therapy

Abstract: Although oncolytic viruses are currently being evaluated for cancer treatment in clinical trials, systemic administration is hindered by many factors that prevent them from reaching the tumor cells. When administered systemically, mesenchymal stem cells (MSCs) target tumors, and therefore constitute good cell carriers for oncolytic viruses. MSCs were primed with trichostatin A under hypoxia, which upregulated the expression of CXCR4, a chemokine receptor involved in tumor tropism, and coxsackievirus and adenov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Utilizing tumor-specific promoters such as CXCR4-promoter allows for tumor-specific transgene expression, driving high expression of therapeutic genes like GM-CSF and B7-1, thereby enhancing immune cell activation and infiltration into tumors [71,102]. Various delivery strategies, including gelatin gel-mediated co-delivery and mesenchymal stem cell-mediated delivery, improve the sustained release and tumor targeting of oncolytic adenoviruses, thereby enhancing their therapeutic efficacy [103,104].…”
Section: Engineering Viruses For Tumor Targetingmentioning
confidence: 99%
“…Utilizing tumor-specific promoters such as CXCR4-promoter allows for tumor-specific transgene expression, driving high expression of therapeutic genes like GM-CSF and B7-1, thereby enhancing immune cell activation and infiltration into tumors [71,102]. Various delivery strategies, including gelatin gel-mediated co-delivery and mesenchymal stem cell-mediated delivery, improve the sustained release and tumor targeting of oncolytic adenoviruses, thereby enhancing their therapeutic efficacy [103,104].…”
Section: Engineering Viruses For Tumor Targetingmentioning
confidence: 99%
“…Combining MSC-delivered OV with prodrug activation is another strategy to achieve optimum effectiveness. Under these circumstances, MSCs might convert the simultaneously delivered prodrug into cytotoxic metabolites, causing oncolysis and inhibiting tumor development without being hazardous to the host's essential organs [ 195 ].…”
Section: Msc-based Delivery Of Oncolytic Adenovirus (Oads)mentioning
confidence: 99%
“…Babaei et al found that MSCs carrying oncolytic reovirus would enhance the anti-tumor activity of a mouse model of CRC (107). Additionally, it was showed that the combination of oncolytic virus delivered by MSCs and prodrug activation could inhibit tumor growth without causing toxicity to the host's vital organs, which would improve the effectiveness and safety of CRC treatment and present a new method for the development of oncolytic virus therapies for cancers (108).…”
Section: Roles Of Mesenchymal Stem Cells In Colorectal Cancermentioning
confidence: 99%